Yield losses in ginger (Zingiber officinale Rosc.) and turmeric (Curcuma longa L.) due to root knot nematode (Meloidogyne incognita) - PATNAIK, PRATIMA RAY, S RAY, K C MOHANTY, S N MOHAPATRA, P R (Journal of Spices and Aromatic Crops, 1995)
Soil application of carbofuran @3 kg a i /ha 3 weeks after planting resulted in avoidable yield losses to the extent of 33.61 per cent in turmeric (Curcuma longa L.) and 26.30 per cent in ginger (Zingiber officinale Rosc.) due to Meloidogyne incognita. Gall index values were correspondingly high in control plots compared to treated ones in both ginger and turmeric.